Estonska učna ura o bralni pismenosti za Slovenijo - Saksida, Igor (Jezik in slovstvo, 2017)
After delineating the results of Slovenian students in the international PISA survey, the article presents a case study of the excellent reading literacy achievements of Estonian students. The Estonian education system takes into consideration other successful education systems: it emphasises a culture of work and high achievements, active teaching and learning methods, the responsibility of all stakeholders (especially teachers), and international benchmarking. In the final part of the article, several recommendations are proposed for Slovenia: it should strengthen school discipline and the authority of the teacher as a reading model, advocating high expectations, equity and quality based on accountability and responsibility (internal and external evaluation related to external assessment); there should also be more pronounced individualisation and differentiation of teaching (especially with more attention devoted to the gifted) and the development of ambitious reading strategies within all subjects, interlaced with diverse reading motivation factors.
Keywords: Estonian Soviet Socialist Republic; Estonija; Slovenia; Slovenija; bralna pismenost; PISA; kakovost pouka bralne pismenosti